2015
DOI: 10.4012/dmj.2014-242
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> microleakage of six different dental materials as intraorifice barriers in endodontically treated teeth

Abstract: The aim of this study was to compare the coronal sealing ability of six different dental materials: Three MTA-based cements and three established restorative materials by in vitro dye penetration method. For in vitro infiltration experiments, seventy extracted single-rooted human teeth were used. After crowns of teeth were reduced, root canals were prepared, and filled with gutta-percha cone. Teeth were randomly divided into 6 groups with 10 teeth per group. The orifice of each tooth was prepared to 3 mm depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…It has been reported that Endocem, the earlier pozzolan-based MTA material, has sealing ability comparable with that of ProRoot MTA 11) . In contrast, Endocem Zr was found to have less favorable sealing ability than other MTA-based materials in a dye penetration study 18) . However, the results of dye penetration studies do not necessarily reflect bacterial invasion 33) , and there are no reports on the mechanical properties of Endocem Zr.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that Endocem, the earlier pozzolan-based MTA material, has sealing ability comparable with that of ProRoot MTA 11) . In contrast, Endocem Zr was found to have less favorable sealing ability than other MTA-based materials in a dye penetration study 18) . However, the results of dye penetration studies do not necessarily reflect bacterial invasion 33) , and there are no reports on the mechanical properties of Endocem Zr.…”
Section: Discussionmentioning
confidence: 99%
“…According to the manufacturer's specifications, 43-46 wt% of Endocem Zr consists of zirconium oxide (Table 1) and this has been shown to have adequate radiopacity. However, a decreased amount of calcium silicate in cement indicates possible shortcomings in terms of calcium ion release 18,30) . Calcium ion release from Portland cement has been reported to decrease on addition of a radiopacifying agent 28,30) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…76,77 EMTA has been demonstrated to have a lower calcium ion concentration than PMTA. 75 EMTA's less favorable sealing ability and initial transient cytotoxicity, 78,79 Figure 1. Flowchart modified from the PRISMA 44 guidelines, demonstrating the process by which the search results were narrowed to the 9 articles included in this systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…76,77 EMTA has been demonstrated to have a lower calcium ion concentration than PMTA. 75 EMTA’s less favorable sealing ability and initial transient cytotoxicity, 78,79 are proposed mechanisms for its poorer performance as compared to PMTA. 2…”
Section: Discussionmentioning
confidence: 99%